DEVIENT BEHAVIOR AND PERSONALITY OF ADOLESCENT (Pedagogy of Higher and Secondary Education, 2022)
The article are considered influence of crisis of teenage age on formation of the person of the teenager and social factors promoting deviation to behaviour.